Abdominal solid organ transplantation : immunology, indications, techniques, and early complications - Pinna, Antonio Daniele; Ercolani, Giorgio (Springer, 2015)
This book is a comprehensive and innovative guide to abdominal solid organ transplantation (SOT). It explains the main immunological problems involved in abdominal SOT, reviews indications for liver, kidney, and small bowel transplantation, and provides detailed descriptions of techniques for procurement and transplantation. In addition, technical, infectious, and immunological complications and their treatment are fully described. Special attention is devoted to the indications for and outcomes of combined kidney-liver and kidney-pancreas transplantation. Clear advice is provided on donor selection and donor safety, and the book concludes by examining medical disease and the risk of solid and hematologic malignancies after transplantation. Abdominal SOT has become the treatment of choice for various end-stage chronic diseases of the liver, kidney, and foregut. Improved knowledge of immunology, the introduction of new immunosuppressive agents, and advances in surgical techniques have all increased the number of potential candidates and led to better outcomes. It is therefore unsurprising that more and more surgeons, physicians, and scientists, as well as students and nurses, are becoming interested in abdominal SOT. This book will provide all practitioners with an excellent, up-to-date summary of knowledge in the field.